2022
DOI: 10.1089/lap.2021.0300
|View full text |Cite
|
Sign up to set email alerts
|

Which Is More Effective: Laparoscopic or Open Partial Cholecystectomy?

Abstract: Objective: In laparoscopic cholecystectomy, partial cholecystectomy is usually preferred when the anatomic exploration is not enough to prevent bile duct injury and other complications. Some surgeons choose laparoscopically to perform partial cholecystectomy, whereas others convert to open surgery. In this study, we aim to discuss and compare the effectiveness of laparoscopic partial cholecystectomy (LPC) and open partial cholecystectomy (OPC). Materials and Methods: The data of 4712 patients who underwent lap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…In recent years, laparoscopic cholecystectomy has been widely used in the clinical treatment of patients with chronic cholecystitis and gallbladder stones [ 25 , 26 ]. As the gold standard for the treatment of gallbladder disease, laparoscopic cholecystectomy has the advantages of being minimally invasive, small incision, less pain, and quicker postoperative recovery, and is conducive to preserving the contractile function of the gallbladder [ 27 , 28 ]. In recent years, extensive research has been undertaken on the treatment of gallbladder stones and chronic cholecystitis [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, laparoscopic cholecystectomy has been widely used in the clinical treatment of patients with chronic cholecystitis and gallbladder stones [ 25 , 26 ]. As the gold standard for the treatment of gallbladder disease, laparoscopic cholecystectomy has the advantages of being minimally invasive, small incision, less pain, and quicker postoperative recovery, and is conducive to preserving the contractile function of the gallbladder [ 27 , 28 ]. In recent years, extensive research has been undertaken on the treatment of gallbladder stones and chronic cholecystitis [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wound infection was the most commonly encountered complication in this review, with an overall incidence of 2.53% in the laparoscopy group, which was far lower than laparotomy. This is consistent with other studies that showed fewer wound infections following laparoscopic procedures, such as appendectomy ( 47 ) and cholecystectomy ( 48 , 49 ). This could be due to the reduced surgical stress and tissue trauma that is imposed on the patient as a result of the minimally invasive approach.…”
Section: Discussionsupporting
confidence: 93%
“…Open subtotal cholecystectomy has been associated to higher risk of reintervention, surgical site infection and 30-day mortality, with lower risk of bile leakage compared to laparoscopic subtotal cholecystectomy (27, 29). Longer operation time, longer postoperative hospital stay and higher incisional hernia rates have also been reported in open subtotal cholecystectomy (29).…”
Section: Should An Open or Laparoscopic Approach Be Used?mentioning
confidence: 94%